2023
DOI: 10.1001/jamanetworkopen.2023.38209
|View full text |Cite
|
Sign up to set email alerts
|

Corticotropin Stimulation in Adrenal Venous Sampling for Patients With Primary Aldosteronism

Shumin Yang,
Zhipeng Du,
Xizi Zhang
et al.

Abstract: ImportanceAdrenal venous sampling (AVS) is usually recommended to distinguish between unilateral and bilateral primary aldosteronism (PA) before definitive surgical or medical treatment is offered. Whether a treatment decision based on AVS with or without corticotropin (ACTH) stimulation leads to different biochemical and clinical remission rates in patients with PA remains unclear.ObjectiveTo evaluate whether treatment decisions based on AVS with or without ACTH stimulation lead to different biochemical and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 45 publications
1
0
0
Order By: Relevance
“…Consistent with our study, most of the studies concluded that in patients who already lateralized with unstimulated sampling, the response to ACTH did not have any impact on surgical outcomes [16,19,26,27,35]. Yang et al [36] designed a randomized controlled trial in which patients were randomly assigned to either the ACTH stimulated or non-ACTH stimulated group when sequential AVS. They found the treatment of primary aldosteronism on the basis of ACTH stimulation did not result in significant differences in biochemical and clinical outcomes.…”
Section: Discussionsupporting
confidence: 84%
“…Consistent with our study, most of the studies concluded that in patients who already lateralized with unstimulated sampling, the response to ACTH did not have any impact on surgical outcomes [16,19,26,27,35]. Yang et al [36] designed a randomized controlled trial in which patients were randomly assigned to either the ACTH stimulated or non-ACTH stimulated group when sequential AVS. They found the treatment of primary aldosteronism on the basis of ACTH stimulation did not result in significant differences in biochemical and clinical outcomes.…”
Section: Discussionsupporting
confidence: 84%